DEVELOPING E-LKM THROUGH 5D MODEL: NEED ANALYSIS - Fadhilah, Nurul; Utami, Yuni Putri; Maghfiroh, Siti (ELTIN Journal, 2024)
The emergence of e-LKM is a technological advancement for Generation Z, whose each day is heavily reliant on technology, allowing the use of e-LKM particularly suited in this digital era. This research aims to examine the need to find an appropriate needs analysis that include the first stage of the 5D model (Define, Design, Demonstrate, Develop, and Deliver). The needs analysis seeks to discover and aims to develop e-LKM based on 1) Students’ target needs, 2) Students’ learning needs, and 3) The perceptions of English lecturers on the e-LKM. The researchers used a questionnaire and distributed it to 240 students.  The result of this study indicated that 1) The student's target needs display that students learn English to be able to communicate and support their future (career and further studies), 2) The student's learning needs point out that students need lecturers and materials as the main source of learning, and 3) The English lecturer perception on students' English language skills are still low and there are gaps between students. This study suggests lecturers create a proper e-LKM for students to use in the learning process since the level of need for e-LKM is quite high.